High-accuracy detection of malaria vector larval habitats using drone-based multispectral imagery - Carrasco-Escobar, Gabriel; Manrique, Edgar; Ruiz-Cabrejos, Jorge; Saavedra, Marlon; Alava, Freddy; Bickersmith, Sara; Prussing, Catharine; Vinetz, Joseph M.; Conn, Jan E.; Moreno, Marta; Gamboa, Dionicia (PLOS Neglected Tropical Diseases, 2019)
Interest in larval source management (LSM) as an adjunct intervention to control and eliminate malaria transmission has recently increased mainly because long-lasting insecticidal nets (LLINs) and indoor residual spray (IRS) are ineffective against exophagic and exophilic mosquitoes. In Amazonian Peru, the identification of the most productive, positive water bodies would increase the impact of targeted mosquito control on aquatic life stages. The present study explores the use of unmanned aerial vehicles (drones) for identifying Nyssorhynchus darlingi (formerly Anopheles darlingi) breeding sites with high-resolution imagery ( 0.02m/pixel) and their multispectral profile in Amazonian Peru. Our results show that high-resolution multispectral imagery can discriminate a profile of water bodies where Ny. darlingi is most likely to breed (overall accuracy 86.73%- 96.98%) with a moderate differentiation of spectral bands. This work provides proof-of-concept of the use of high-resolution images to detect malaria vector breeding sites in Amazonian Peru and such innovative methodology could be crucial for LSM malaria integrated interventions.